The Impact of TikTok on Generation Z's Mental Health - Al Wafah, Ahmad Ryan; Ningsih, Yusria (Universitas Ibn Khaldun, 2025)
TikTok is a platform that allows users to express their creativity or interests by uploading videos to the main page, often referred to as FYP (For You Page). The use of TikTok social media among Generation Z may affect their mental health. Therefore, it is important to understand how social media, and TikTok in particular, can impact the mental health of users, especially generation Z. This study examined the influence of TikTok on generation Z's mental health. This study examines the influence of TikTok on Generation Z's mental health. This research was conducted by conducting interviews with generation Z and then analyzed using a descriptive approach. The results showed that TikTok social media can have both positive and negative impacts on Generation Z's mental health. It has a positive impact when used to access content that contains motivation, positive experiences of others, increase income and content that is educational in nature. It has a negative impact when used to access dangerous or negative things, follow unhealthy trends and challenges and excessive use.